Development and validation of medical students' digital health competencies scale - Ahmad, Zulkhairul Naim Sidek (2024)
Digital health offers numerous advantages, including increased access to care, cost reduction, enhanced efficiencies, improved patient satisfaction, and higher-quality care. As a result, medical students' digital health competence is an important area to study as the healthcare sector landscape changes globally. However, no instruments with psychometric evidence of validity and reliability depict digital health skills have been examined among medical students in Malaysia. Therefore, the present study aimed to develop and validate the Medical Students' Digital Health Competencies Scale (MS-DHCS). A study was done to develop and validate a questionnaire that consisted of five stages: domain identification, item generation, content validation, face validation, and internal structure assessment. Domain identification through literature review was conducted by the main researcher, item generation through literature review, content validation involved six content experts and face validation involved 10 medical students from Universiti Malaysia Sabah (UMS). A total of 160 MS-DHCS 3.0 forms containing 32 items were distributed for the internal structure assessment. EFA was conducted and Principal Axis Factoring (PAF) was used as an extraction method in EFA. Reliability was checked using Cronbach Alpha values. Three domains were identified for MS-DHCS and 39 items were generated for MS-DHCS 1.0. Content validation of 39-items MS-DHCS 1.0 revealed an S-CVI/Ave of 0.96 after two rounds review and face validation of 32-items MS-DHCS 2.0 revealed an S-FVI/Ave of 0.97 and MS-DHCS 3.0 were distributed to 160 medical students for internal structure assessment. EFA yielded three factors namely knowledge, skills and attitudes which cumulative percentage of variance of 51.7% to 62.6%. The range for factor loading for knowledge, skills and attitudes were 0.61-0.77, 0.69-0.87 and 0.59 – 0.77, respectively. The internal consistency was good to excellent with Cronbach's alpha ranging from 0.88 to 0.92 for all domains. In conclusion, the 32 items – MS-DHCS is deemed valid and reliable to measure resilience among medical students. However, any attempt to generalize the findings to medical students in different settings should be done with cautious and further validation study need to be carried out.